Respon Stek Cabang Bambu Betung (Dendrocalamus asper) Terhadap Pemberian Zpt Alami - Mariana Marambahmeha; Mamie E. Pellondo’u; Pamona Silvia Sinaga (Wana Lestari, 2023)
Betung bamboo is widely used for building construction materials, furniture, and has ecological benefits because it is hard and strong. Bamboo propagation can be done generatively and vegetatively. Generative propagation has weaknesses, namely bamboo seeds are very difficult to obtain, seed viability is low, seeds cannot be stored for long, are susceptible to pests and diseases, and require a very long time to reach the age of the first harvest. Regulatory substances that can be used to encourage the growth of bamboo branch cuttings are shallots and banana weevils. The study was arranged in a completely randomized design (CRD) with 9 treatments namely A0 (control), A1 (25% banana weevil), A2 (50% banana weevil), A3 (75% banana weevil). banana), A4 (100% banana weevil), A5 (25% shallot), A6 (50% shallot), A7 (75% shallot), A8 (100% shallot). The results showed that natural ZPT (banana and shallot weevils) had no significant effect on the growth of betung bamboo branch cuttings. Although no treatment had a significant effect, when viewed from the average value of each parameter, it can be said that the treatment of natural ZPT concentrations on bamboo betung branch cuttings was in treatment A8 (100% shallot concentration) for the parameter of the period of shoot emergence, treatment A6 (50% shallot concentration) for the number of leaves parameter, treatment A0 (control) for the root length parameter and for the parameter living percentage of bamboo betung branch cuttings showed the highest average for all treatments.